3E analysis of a biomass-to-liquids production system based on solar gasification. (15th February 2021) - Zhong, Dian; Zeng, Kuo; Li, Jun; Yang, Xinyi; Song, Yang; Zhu, Youjian; Flamant, Gilles; Nzihou, Ange; Yang, Haiping; Chen, Hanping
Abstract: The solar gasification system (SGS) and traditional system are modeled by Aspen Plus. And their energetic, economic as well as ecologic (3E) performance are compared. The effects of different feedstocks and Direct Normal Irradiance (DNI) to the productivity and efficiency of SGS are also carried out. The results show that a biomass-based, solar-assisted liquid fuel production system offers a productivity increasing potential of 49.44% more refined syngas and 65.74% more liquid fuels due to its higher utilization of feedstock. And for the same reason, the energetic performance of SGS increases from 40.22% to 40.66% for thermal efficiency and from 38.35% to 41.35% for exergy efficiency compared with those of reference system. The final price of products in SGS could only be equal to that of reference system when the carbon tax is under considering, while both of them shows no superiority to that of petroleum products. SGS has a better ecology performance contributed by less total carbon and water footprints which are only 55.27% and 61.34% of those of the reference system. Highlights: 3E analysis was used to evaluate the solar gasification biofuel production system. Solar gasification system (SGS) exhibited higher productivity and exergy efficiency. The efficiency performance of SGS under different conditions were estimated. Carbon and water footprint of SGS were 44.73% and 38.66% lower. SGS will be competitive when carbon tax reaches 551.42 CNY/t.